Reading a Report Text by Snowball Throwing: Strategy to Enhance Students’ Comprehension - Adawiyah, Robiatul; Hikmah, Durratul; Muslim, Imam (Jurnal Penelitian Pendidikan, 2025)
This Classroom Action Research (CAR) aims to evaluate the effectiveness of the Snowball Throwing strategy in improving reading comprehension of report texts among ninth-grade students at MTsN 1 Probolinggo. Additionally, this study also determines the extent of improvement in student learning outcomes. This research addresses the issues of low reading skills and passive learning behavior among students. Initially, the learning pass rate was only 24%. Conducted in the odd semester of the 2025/2026 academic year, this study involved 25 students from class IX D. This study followed Kemmis and McTaggart's (2014) cyclical CAR model, which included a pre-cycle, Cycle I, and Cycle II. Quantitative data were obtained from pre-tests and post-tests, while qualitative data were obtained from observations and field notes. The results of the study showed a significant increase in student learning outcomes. The average score increased from 48.0 in the pre-cycle to 72.6 in Cycle I, and peaked at 88.8 in Cycle II. The learning completion rate reached 100% in Cycle II, exceeding the success indicator of 80%. Qualitatively, students became more active, confident, and demonstrated better collaboration skills. Therefore, the Snowball Throwing strategy has proven to be very effective in improving report text comprehension and creating an interactive learning environment. Therefore, it is recommended that future research explore the effectiveness of this strategy on different types of texts or specific reading skills, such as inference.